Numerical study of natural convection in asymmetrically heated channel considering thermal stratification and surface radiation. (2nd November 2017) - Ramalingom, Delphine; Cocquet, Pierre-Henri; Bastide, Alain
ABSTRACT: This article consists in a numerical study of the influence of thermal stratification and surface radiation on laminar airflow induced by natural convection in vertical, asymmetrically heated channels. Several cases are investigated to spotlight their influence on fluid dynamics and thermal quantities. Thermal stratification is obtained by a weak gradient of temperature outside of the channel, and then the temperature at the bottom end of the channel is considered as a function of time. Significant effects on vertical velocities, mass flow, and flow structure are shown. Surface radiation is also considered but appears less predominant than thermal stratification for the selected conditions of this article. The impact on heat transfer is also evaluated for each studied configuration. It is observed that local and mean Nusselt numbers weakly increase for the investigated cases.